Complaints of insomnia in different occupations. - Partinen, Markku; Eskelinen, Leena; Tuomi, Kaija (Scandinavian Journal of Work, Environment & Health, 1984)
Complaints of insomnia were inquired about in a questionnaire survey of 6 268 persons (2 801 men; 3 467 women, mean age 50.5 years, range 45-57 years) in 40 different occupational groups. Among bus drivers 18.9% complained of having rather or very much difficulty falling asleep. Among female cleaners, male teachers, male directors, and male physicians the respective percentages were 18.8, 18.0, 3.7, and 4.9. Disturbed nocturnal sleep was complained of the most often by male laborers (28.1% waking up at least three times a night), female cleaners (26.6%) and female hospital aides (26.4%). Disturbed nocturnal sleep was rare among male physicians (1.6%), male directors (7.4%), female head nurses (8.9%), and female social workers (9.4%). Complaints of waking up too early in the morning were the most common among female laborers (13.2% often or always), male construction workers (9.1%), and female cleaners (8.4%). They were rare among male physicians (1.6%), male directors (1.8%), nurses in outpatient wards (1.2%), and female bathers (2.0%). Sleeping pills were used the most frequently by male gardeners (7.1% were frequent or habitual users), female social office workers (5.8%), and male construction workers (5.4%). Some aspects of work which could explain the differences are discussed.